ASSESSMENT OF NURSES’ KNOWLEDGE FOR THE TREATMENT OF PREGNANCY-INDUCED HYPERTENSION IN THE LADY WALLINGTON HOSPITAL, LAHORE, PAKISTAN: A DESCRIPTIVE STUDY - Asia Shahzadi; Nabila Jamil; Sadaf Noureen; Sakina Parveen; Samina Bibi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Pregnancy-induced hypertension (PIH) is a leading cause of maternal death, newborn morbidity and mortality, and the most common pregnancy complication.Objective: Assess the knowledge and understanding of nursing staff at Lady Wallington Hospital about pregnancy-induced hypertension to identify educational gaps and opportunities for quality improvement in patient care.Methods: A descriptive study was conducted at Lady Wallington Hospital in Lahore, where a purposive sample of 100 nurses from the Gynecology Ward, emergency department, and medical wards completed standardized self-report surveys, providing data on their knowledge and understanding of pregnancy-induced hypertension.Results: The study's demographic analysis showed that most participants (80%) were between 31-39 years old, with a slight majority being female (56%) and unmarried (56%). The majority (52%) held a nursing degree, and half (50%) had 11-20 years of nursing experience. Notably, the results revealed a satisfactory level of knowledge regarding gestational hypertension among the nurses, indicating a solid understanding in this vital area of care.Conclusion: The study concluded that nurses exhibited a satisfactory level of knowledge regarding pregnancy-induced hypertension, indicating they are well-prepared to provide quality care and support to affected patients.